Universalizing science literacy: How to transcend deficit models of teaching and learning - Brabazon, Tara; Quinton, Jamie; Hunter, Narelle (International Journal of Research in STEM Education, 2023)
Student attrition figures are a hidden metric in universities.  They signify institutional failure, inhibit branding and marketing campaigns, and displace blame onto individual students. Behind the thousands of cases of attrition are individual stories of shame, guilt, failure, confusion, and lost future hopes and aspirations. This article explores how students' in and through their diversity - can be supported to succeed. Critiquing the deficit model of teaching and learning and deploying both universal design and the abundance model of teaching and learning, this article provides new strategies for student success. We offer innovative methodologies to understand and enable productive pathways by students through a curriculum. The goal is to enhance and enliven science education and demonstrate the gift and power of well-qualified university academics aligning innovative research and teaching.